Semiotic Meanings in Cigarette Advertisement Texts - Rodearta Purba; Zainuddin - -; Amrin - Saragih (LINGUISTIK TERAPAN, 2020)
Semiotic is the study of sign or the science that study about the sign in human beings. The objectives of this study were to investigate the semiotic meanings applied in cigarette advertisement, to analyze how the meanings were coded verbally and non-verbally, and to reason why it is used in the ways they are. The data for the study were clauses, phrases, and sentences drawn from selected billboard advertisement of cigarette in Medan. The verbal data analyzed with linguistic devises and textual analysis of Leech Theory and visual grammar of Kress and Van Leeuwen as theoretical framework. The result were two broad categorize of meaning. They were related to verbal and non-verbal aspects. The relation between the verbal and non-verbal expression were elaborate, manipulate, and exageratte,  the advertisers make the major use of declarative sentence that are found on 11 texts. Then, by using 8 imperative and 8 adjective. Next, by using 6 disjunctive and 6 noun/pronoun. In image/picture use of visual features such as calor saturation, symbolic structure representation, offering gaze, the use of large size, logo, slogan. Various social context were discoverd in the advertisement such as promoting the standar of quality, quantity, creative, enjoying the life. The standard idea about how particular mode like young and old man should be differentiated based on the conventional values in society when it comes to what types of product that is competible to them. Cigarette advertisement also hide threats with persuasive expression and colorful meaning for commercial purposes.Keywords: Semiotics, Sign, Critical Discourse Analysis, Cigarette Advertisement.